2020
DOI: 10.23822/eurannaci.1764-1489.128
|View full text |Cite
|
Sign up to set email alerts
|

Tree Nuts Anaphylaxis in Preschool Age Children

Abstract: Introduction: The incidence of food-induced anaphylaxis (FIA) is increasing in young children. Although the commonest culprits are cow's milk and egg, FIA to tree nuts (TNs) have been increasing. Objective: Characterization of children referred to our allergy department due to TNs-induced anaphylaxis (TNs-FIA) during preschool age. Materials and Methods: We have retrospectively included 25 children with clinical history of preschool TNs-FIA, proven by allergological work-up. TNs sensitization was assessed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
0
10
2
Order By: Relevance
“…These results diverge from other European studies, where hazelnut was the most common TN 8,15 . In a recent Portuguese case series in children at pre‐school age, cashew and walnut were also the most common TNs 17 . FIA has important repercussions in quality of life, as contact with food allergens, even in trace amounts, as hidden or cross‐reacting allergens, may be life‐threatening.…”
Section: Discussionmentioning
confidence: 62%
“…These results diverge from other European studies, where hazelnut was the most common TN 8,15 . In a recent Portuguese case series in children at pre‐school age, cashew and walnut were also the most common TNs 17 . FIA has important repercussions in quality of life, as contact with food allergens, even in trace amounts, as hidden or cross‐reacting allergens, may be life‐threatening.…”
Section: Discussionmentioning
confidence: 62%
“…TNs-induced anaphylaxis has been increasingly reportedworldwide, in particular in preschoolers [14,23,24,26].In this case-series, TNswere an importantcause of FIA,being the second cause inchildren; walnut and cashewwere the most commonreportedTNs. These results diverge from other European studies,where hazelnut was the most frequent TN [8,24].In a case-series reported from a single center in our country, in Coimbra, TNs were the main cause of FIA in adults, especially walnut and hazelnut [27].By contrast, in arecent study also conducted in our country, involving preschoolers, cashew and walnut were the commonestTNs [26]. LTPsare a common cause of FIA in the Mediterranean area [9,[28][29][30],and have been pointed out as the main elicitor of FDEIA [28,30,31].Food management in these patients is challenging [30][31][32],due to the presence of these panallergens in a great number of plant foods,like fresh fruits, vegetables, TNs and seeds.In studies conducted in Italy [28] and Spain [32], LTPs are reported as the main cause of FIA in adults, especially peach.…”
Section: Discussionmentioning
confidence: 67%
“…Labeling and education of patients and caregivers areessential for allergen avoidance [4,23]. TNs-induced anaphylaxis has been increasingly reportedworldwide, in particular in preschoolers [14,23,24,26].In this case-series, TNswere an importantcause of FIA,being the second cause inchildren; walnut and cashewwere the most commonreportedTNs. These results diverge from other European studies,where hazelnut was the most frequent TN [8,24].In a case-series reported from a single center in our country, in Coimbra, TNs were the main cause of FIA in adults, especially walnut and hazelnut [27].By contrast, in arecent study also conducted in our country, involving preschoolers, cashew and walnut were the commonestTNs [26].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Both age distribution and type of allergens (triggers) were comparable with the Anaphylaxis Registry showing that food such as cow’s milk and hen’s egg caused 88% of reactions in children younger than 6 years, as well as other studies in the youngest children with anaphylaxis history [ 17 19 ]. An increasing number of paediatric reports indicated a growing role and strong allergic potential of the nuts, in particular tree nuts in the preschool children who developed allergic reactions to cashews and walnuts independent from their peanut or legumes allergy [ 20 22 ]. In our material, the tree nuts such as hazelnuts, walnuts, and cashews ( n = 6) caused an anaphylactic reaction in children aged 0–10 years twice more often than peanuts.…”
Section: Discussionmentioning
confidence: 99%